Observations of a radio-bright, X-ray obscured GRS 1915+105. Issue 1 (24th February 2021) - Motta, S E; Kajava, J J E; Giustini, M; Williams, D R A; Del Santo, M; Fender, R; Green, D A; Heywood, I; Rhodes, L; Segreto, A; Sivakoff, G; Woudt, P A
ABSTRACT: The Galactic black hole transient GRS 1915+105 is famous for its markedly variable X-ray and radio behaviour, and for being the archetypal galactic source of relativistic jets. It entered an X-ray outburst in 1992 and has been active ever since. Since 2018 GRS 1915+105 has declined into an extended low-flux X-ray plateau, occasionally interrupted by multiwavelength flares. Here, we report the radio and X-ray properties of GRS 1915+105 collected in this new phase, and compare the recent data to historic observations. We find that while the X-ray emission remained unprecedentedly low for most of the time following the decline in 2018, the radio emission shows a clear mode change half way through the extended X-ray plateau in 2019 June: from low flux (∼3 mJy) and limited variability, to marked flaring with fluxes two orders of magnitude larger. GRS 1915+105 appears to have entered a low-luminosity canonical hard state, and then transitioned to an unusual accretion phase, characterized by heavy X-ray absorption/obscuration. Hence, we argue that a local absorber hides from the observer the accretion processes feeding the variable jet responsible for the radio flaring. The radio–X-ray correlation suggests that the current low X-ray flux state may be a signature of a super-Eddington state akin to the X-ray binaries SS433 or V404 Cyg.